Absolute burnup measurement of LEU silicide fuel plate irradiated in the RSG GAS multipurpose reactor by destructive radiochemical technique. (November 2015) - Ginting, Aslina Br.; Liem, Peng Hong
Highlights: LEU silicide fuel absolute burnup measurement by destructive radiochemical technique. The absolute burnup of a sample taken for a fuel plate irradiated in the Indonesian RSG GAS was measured. U-235 and Cs-137 isotopes were taken as the burnup indicator. Burnup verification was conducted using SRAC2006 and JENDL-3.3 based library. An excellent agreement between the measured and calculated values was confirmed. Abstract: Absolute burnup measurements of a sample taken from the IDA0045 fuel plate of RI-SIE2 low enriched uranium, silicide, experimental fuel element irradiated in the Reaktor Serba Guna G.A. Siwabessy (RSG GAS; previous name MPR-30) multipurpose reactor were conducted using destructive radiochemical technique. The destructive burnup measurement effort is an important part of the continuing efforts related to the post irradiation examination (PIE) project of the Indonesian National Nuclear Energy Agency. The amount of U-235 fissile material left and the Cs-137 fission product in the sample were selected as the burnup indicator for the present work. The measured burnup values of the sample were 72.4 ∓ 4.5% loss of U-235 and 78.6 ∓ 5.0% loss of U-235 based on the amount of U-235 fissile material and Cs-137 fission product, respectively. The burnup value based on the measured Cs-137 showed an overestimation since it was assumed that all fissions originated from U-235 thermal fissions. Numerical burnup verification was also conducted using the SRAC2006 code system with a PIE dedicated detail burnup chain and a SRAC library based on the JENDL-3.3 nuclear data. The verification results, combined with the previous nondestructive burnup measurement results on the plate wise and axial distributions of the Cs-134/Cs-137 activity ratio, produced burnup value of 75.0 ∓ 5.0% loss of U-235 which agreed well with the measured values.